MULTIDISCIPLINARY APPROACH IN THE TREATMENT OF SQUAMOUS CELL CARCINOMA AT REGIO GLOSSUS - Tri Nurrahman; Seto Adiantoro; Kiki Akhmad Rizki; Farah Asnely (FKG Unlam, 2020)
ABSTRACTBackground: Squamous Cell Carcinoma (SCC) is the most common case of oral cancer which often occurs laterally on the tongue and rarely develops on the dorsal surface of the tongue. More than half of the cases are diagnosed late, thereby reducing the survival rate of the patients. Objective: This report was intended as an evaluation for the management of squamous cell carcinoma under multidisciplinary approach between oral surgery and other departments, as well as the provision of further post-operative treatment. Case Report: The author presents a case of 68-years-old female patient with a lump and an ulcer on her tongue. Around six months prior to the visit, patient complained of tongue ulcer followed by the emergence of a lump in a size of a corn seed. The lump was gradually enlarged with constant widening of the ulcer. Pain on the tongue was also perceived. The patient was then referred to Hasan Sadikin Hospital for further treatment. Case Management: Patients underwent hemiglossectomy and Selective Neck Dissection (SND) surgical procedures performed by Oral and Maxillofacial Surgeon in collaboration with Surgical Oncologist. Furthermore, after surgery, the patient was consulted to the Hemato-Oncology Division of Internal Medicine Department for chemotherapy treatment. Conclusions: The exact diagnosis was made based on the histopathological biopsy results of the tongue tissue. Management of tongue cancer must be done multidisciplinary. Some things that must be considered in handling such cases are the eradication of the tumor, the return of oral cavity function, and the aesthetic/functional aspects of the patient. Keywords: Oral cancer, Squamous cell carcinoma, Tongue cancer